Memorial dedicated to Alexander Cumine Peat - Ghosh, Ayan (2023)
Memorial erected to Alexander Cumine Peat, Major in the Corps of Engineers at Bombay, who died at Currachee (Karachi) on 15th April 1848, aged 46. The memorials serve as markers of the expanding territories of the Bombay Presidency, which by the late 19th century came to include parts of Sindh Province (1847–1935) and Aden, now part of Yemen (1839–1932).